IsomiR_Window : a system for analyzing small‑RNA‑seq data in an integrative and user‑friendly manner - Vasconcelos, Ana M. (2021)
Research Areas: Biochemistry & Molecular ; Biology Biotechnology & Applied ; Microbiology ; Mathematical & Computational Biology